PREVALENCE OF INHERITED THROMBOPHILIA IN PATIENTS WITH SEVERE OVARIAN HYPERSTIMULATION SYNDROME - Machac, Stepan; Lubusky, Marek; Prochazka, Martin; Streda, Robert (Biomedical papers, 2006)
Background and objective: To determine the prevalence of markers of inherited thrombophilia in patients with severe form of ovarian hyperstimulation syndrome (OHSS) Design and methods: Blood samples were analysed for markers of thrombophilia (mutation of factor V - Leiden, mutation of methylentetrahydrofolat reductase (MTHFR) C677T and mutation of prothrombin G20210A). The study group consisted of women who had undergone controlled ovarian hyperstimulation for IVF complicated by severe OHSS (group A, n = 50). Results were compared with two controls groups - women who underwent ovarian hyperstimulation for IVF without developing OHSS (group B, n = 93) and healthy pregnant women with no history of infertility (group C, n = 196).Results: We have found 7 out of 50 patients from group A positive for Leiden mutation (heterozygous) 11 out of 93 from group B (heterozygous), p = 0.71 OR 1.21 (0.39 3.70) and 10 out of 196 from group C (heterozygous), p = 0.03 OR 3.03 (0.97 9.28). Polymorphism of MTHFR 677T gene was detected in 17 out of 50 patients (heterozygous) from group A, in 36 out of 93 patients from group B (35 heterozygous, 1 homozygous) and in 93 out of 196 patients from the group C (86 heterozygous, 7 homozygous) with no statistical significance.Conclusions: We found an increased prevalence of factor V Leiden mutation in Czech infertile women. However carriers of Leiden mutation had no enhanced risk of development severe form of OHSS during stimulation.
Keywords: Ovarian hyperstimulation syndrome/Thrombophilia/Factor V Leiden mutation